A search for pulsations in two Algol-type systems V1241 Tau and GQ Dra - Ulaş, Burak; Ulusoy, Ceren; Gazeas, Kosmas; Erkan, Naci; Liakos, Alexios (Precision Asteroseismology, 2014)
We present new photometric observations of two eclipsing binary systems, V1241 Tau and GQ Dra. We use the following methodology: initially, the Wilson-Devinney code is applied to the light curves in order to determine the photometric elements of the systems. Then, the residuals are analysed using Fourier techniques. The results are the following. One frequency can be possibly attributed to a real light variation of V1241 Tau, while there is no evidence of pulsations in the light curve of GQ Dra.
Keywords: Astrophysics - Solar and Stellar Astrophysics; Stars: binaries: eclipsing; stars: oscillations (including pulsations)